Ultrasonogram of hepatocellular carcinoma is associated with outcome after radiofrequency ablation - Moribata, Kosaku (Baishideng Publishing Group Co., Limited, 2012)
AIM: To investigate the association between B-mode ultrasound classification of small hepatocellular carcinoma (HCC) and outcome after radiofrequency ablation (RFA). METHODS: Ninety-seven cases of HCC treated using RFA between April 2001 and March 2006 were reviewed. Ultrasound images were classified as follows: type 1, with halo (n = 29); and type 2, without halo (n = 68). Type 2 was further categorized into three subgroups: type 2a, homogenous hyperechoic (n = 9); type 2b, hypoechoic with smooth margins (n = 43); and type 2c (n = 16), hypoechoic with irregular or unclear margins. Patients with type 2a HCC were excluded from analysis due to the small number of cases. RESULTS: Two year recurrence rates for type 2b, type 1 and type 2c were 26%, 42% and 69%, respectively, with significant differences between type 2b and type 2c (P < 0.01), and between type 1 and type 2c (P < 0.05). Five year survival rates were 89%, 43% and 65%, respectively. Survival was significantly longer for type 2b than for other types (type 1 vs type 2b, P < 0.01; type 2b vs type 2c, P < 0.05). On univariate analysis, factors contributing to recurrence were number of tumors, tumor stage, serum level of lens culinaris agglutinin-reactive alpha-fetoprotein and ultrasound classification (P < 0.05). Factors contributing to survival were tumor stage and ultrasound classification (P < 0.05). Multivariate analysis identified ultrasound classification as the only factor independently associated with both recurrence and survival (P < 0.05). CONCLUSION: B-mode ultrasound classification of small HCC is a predictive factor for outcome after RFA.